Evaluating Public and Industry Compliance with Standards Organisation of Nigeria’s Regulations for Safety and National Development in Jabi, Abuja - Igbaba, Sunday Ogbu Igbaba; Nta, Dominic Agnes Nta (African Journal of Stability and Development (AJSD), 2025)
This study evaluated the awareness, compliance, and implications of the Standards Organisation of Nigeria’s (SON) regulations among industries and the public in Jabi, Abuja. It addressed the challenges of inadequate public and industry understanding of SON’s standards, which hinder compliance and pose risks to consumer safety and national development. Drawing on Public Awareness Theory and Stakeholder Theory, the research investigated the role of effective communication and collaborative stakeholder engagement in fostering regulatory adherence. A descriptive survey design was adopted, targeting Jabi residents, Julius Berger construction company, SON officials, and consumers. A sample of 383 respondents was selected through stratified random sampling. Data were collected using structured questionnaires and analysed with descriptive and inferential statistical techniques. Findings indicated moderate public awareness and varying levels of industry compliance, constrained by ineffective communication, resource limitations, and technical gaps. Non-compliance was associated with the production of substandard products, which compromises consumers’ safety. The study recommended enhancing SON’s enforcement mechanisms, conducting regular workshops for industries, and launching targeted awareness campaigns using diverse communication channels. Collaborations with stakeholders, including law enforcement and industry associations, were also advised to strengthen compliance and protect consumers.